2021
DOI: 10.1101/2021.11.02.21265805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causes, characteristics, and patterns of prolonged unplanned school closures prior to the COVID-19 pandemic – United States, 2011 – 2019

Abstract: IntroductionOutside of pandemics, there is little information about occurrence of prolonged unplanned K-12 school closures (PUSC). We describe here the reasons, characteristics, and patterns of PUSC in the United States during 8 consecutive inter-pandemic academic years, 2011-2019.MethodsFrom August 1, 2011 through June 30, 2019, daily systematic online searches were conducted to collect data on publicly announced unplanned school closures lasting ≥1 school days in the United States. Closures were categorized … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…20 , 26 , 27 The annual occurrence of prolonged unplanned school closures (≥ 5 school days) before the COVID-19 pandemic further supports the need for the timely development of effective high-quality distance learning tools. 28 Distance learning strategies require several components to be successful, including a learning management system, policies to address student access to devices and to the Internet, and high-quality online course content, as well as adaptation of content to student learning needs, and training and support for teachers to deliver instruction online. 29 K-12 teachers who transitioned to distance learning during the COVID-19 pandemic reported that support would have been helpful in the following areas: previous training on learning management system, student internet and computer access, more time to prepare for distance learning, better guidance on platforms and tools to use, and teaching resources available for distance learning.…”
Section: Discussionmentioning
confidence: 99%
“…20 , 26 , 27 The annual occurrence of prolonged unplanned school closures (≥ 5 school days) before the COVID-19 pandemic further supports the need for the timely development of effective high-quality distance learning tools. 28 Distance learning strategies require several components to be successful, including a learning management system, policies to address student access to devices and to the Internet, and high-quality online course content, as well as adaptation of content to student learning needs, and training and support for teachers to deliver instruction online. 29 K-12 teachers who transitioned to distance learning during the COVID-19 pandemic reported that support would have been helpful in the following areas: previous training on learning management system, student internet and computer access, more time to prepare for distance learning, better guidance on platforms and tools to use, and teaching resources available for distance learning.…”
Section: Discussionmentioning
confidence: 99%